The Covers of Young Adult Novels and Their Graphic Novel Adaptations: A Qualitative Multimodal Content Analysis. (November 2020) - Kachorsky, Dani; Reid, Stephanie F.
Drawing from theories of visual culture, social semiotics, and multimodality, the researchers conducted a qualitative multimodal content analysis of the covers of 21 young adult (YA) books that had been adapted as graphic novels (GNs). This study showed that the GN covers emphasized character and that the ages of the represented characters seemed to shift during the process of adaptation. However, publishers linked the two covers through branding, color schemes, and visual elements. These findings suggest that publishers view the readership of GNs differently than the readership of YA novels. This article encourages literacy education researchers and classroom practitioners to support students in analyzing visual artifacts designed for particular consumers. Critical readers could examine the sites of production and dissemination in addition to the text itself.